Упрастите выражение!
а) ( m+4)²-5m(2-4m)
б) (5-y)²-(y-2)*(y+3)
С объяснением !!

Ddaannjjdb Ddaannjjdb    2   24.05.2021 17:08    0

Ответы
анель106 анель106  23.06.2021 17:10

Объяснение:

а)

{m}^{2} + 8m +1 6 - 10m + 20m^{2} = 21{m}^{2} - 2m + 16

б)

25 - 10y + {y}^{2} - ( {y}^{2} + 3y - 2y - 6) = 25 - 10y + {y}^{2} - {y}^{2} - 3y + 2y + 6 = 31 - 11y

ПОКАЗАТЬ ОТВЕТЫ
livanatalya livanatalya  23.06.2021 17:10
А) =m^2+8m+16-10m+20m^2= 21m^2-2m+16
б) =25-10у+у^2-(у^2+3у-2у-6)=25-10у+у^2-(у2+у-6)=25-10у+у^2-у^2-у+6=31-11у
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра